Follow Up Data of MRI-Visible Synthetic Meshes for Reinforcement in Large Hiatal Hernia in Comparison to None-Mesh Repair—A Prospective Cohort Study - Weyhe, Dirk; Klinge, Uwe; Uslar, Verena Nicole; Tabriz, Navid; Kluge, Alexander (Frontiers in Surgery, 2019)
Background: Mesh augmentation for large hiatal hernia is still controversial because of high alleged risk of chronic reaction or shrinkage of mesh orifice surrounding the esophagus. The aim of this cohort study was to develop and establish an image analysis scheme, including 3D reconstruction, for MRI-visible meshes (DynaMesh®) to measure postoperative mesh shrinkage in order to observe potential complications. Methods: Between 12/2012 and 10/2016, n=33 patients underwent surgery to correct symptomatic hiatal hernia (implantation indicated: n=18). Intraoperative measurement of the hiatal surface area (HSA) > 5cm2 was indication for mesh implantation. Early postoperatively, and during long-term follow-up, MRI was performed and patients filled out the gastrointestinal quality of life index (GIQLI score). Results: Follow-up rate was 76%(n= 25/33). Overall recurrence rate was 4%(1/25). No other patient showed reflux or dysphagia symptoms. Mesh related complications were not observed during follow-up period. Median GIQLI score of patients with mesh was 123(range: 67-144), and 93(52-141) for patients without mesh. Comparison of early and mid-term postoperative MRI for patients with mesh showed changes in mesh orifice size of 3% (corresponding to a slight increase in size of about 6mm2) without any significant correlations with BMI, HSA, or patient age. Conclusion: We established an image analysis and 3D reconstruction scheme for MRI visible meshes in hiatal hernia repair. MRI images of normal clinical quality are sufficient for this analysis. Mesh orifice size in MRI-visible meshes does not seem to change at a clinically relevant level in the small cohort observed here. Further studies of large cohorts are necessary to establish if HSA >5cm2 could be a suitable measure for indication of mesh implantation.